Land gradient and configuration effects on yield, irrigation amount and irrigation water productivity in rice-wheat and maize-wheat cropping systems in Eastern India - Devkota, Krishna Prasad; Yadav, Sudhir; Humphreys, E.; Kumar, Akhilesh; Kumar, Pankaj; Kumar, Virender; Malik, R.K.; Srivastava, Amit K. (Elsevier, 2021)
Laser land levelling is expanding rapidly in the rice-wheat (RW) and maize-wheat (MW) systems of the IndoGangetic Plains of India and Pakistan. Current practice is to level to zero (0%) gradient, whereas a small gradient (e.g. 0.1%) is typically used in developed countries. Therefore, experiments were conducted in farmers' plots (-15 m x 40 m) in the Eastern Gangetic Plains to evaluate laser levelling with a 0.1% gradient in comparison with 0% and farmer levelling practice (FL). The study was conducted over two years in RW and MW systems. In the MW system, raised beds in plots lasered with 0% and 0.1% gradients were also evaluated. Laser levelling with 0% gradient significantly reduced irrigation amount and/or increased irrigation water productivity (WPi) in all crops/systems grown on the flat compared to FL except for wheat in the MW system. While there was a consistent trend for higher yield with a 0% gradient compared with FL, the differences were not significant in any crop/system. For the RW system, the results suggest no to marginal benefits in irrigation amount and WPi from levelling with a 0.1% gradient in comparison with 0% gradient. In that system, by far the bigger gains were from changing from FL to laser levelling with 0% gradient. This resulted in substantial reductions in irrigation amount, which greatly increased WPi in both crops (by -40%), while yield was not affected. Rice grown with FL was not profitable, but lasering with 0% gradient significantly increased gross margin for rice, wheat and the total RW system. As for the RW system, levelling to 0% with a flat configuration significantly increased WPi of both crops in the MW system compared to FL, but by a lesser proportion. Raised beds significantly increased yield of maize by 8% (0.5 t ha-1), reduced irrigation amount by 20% (40 mm) and increased WPi by 34% (1.0 kg m-3) in comparison with the laser levelled flat plots. Gross margin of the MW system on beds was 17-20% higher than FL, and gross margin with beds on a 0.1% gradient was significantly higher than either gradient on the flat. The results suggest that the gains from levelling with a 0.1% gradient compared to 0% are marginal; however, this may change if the goal of consolidation of small farmer plots into larger fields becomes a reality provided there is a proportionate increase in irrigation flow rates, and ability to drain